Determinants of Traditional Contraceptive use among Women - Ike Fitrah Atul Chabibah; Yekti Satriyandari (Women, Midwives and Midwifery, 2022)
Background: Population growth in Indonesia remains high and itconstitutes a population problem which requires the enactment of population policy, namely by reducing the growth rate as low as possible through the family planning programs. 3.8% of women of childbearing age (WCA) in Indonesia still choose to use the traditional family planning methods, including the use of natural ingredients or herbal medicine as the traditional contraception, the use of coitus interruptus method, and the use of calendar method which is lower in effectiveness than modern contraceptive methods.